EXPLORING RELATIONSHIP BETWEEN READING AND WRITING SKILLS IN EFL STUDENTS - Yesi (Cirebon International Conference on Education and Economics Proceeding, 2024)
This study investigates the correlation between reading and writing skills among English as a Foreign Language (EFL) students. The method of the study is quantitative method. A sample of 58 students was selected using a non-probability sampling technique to determine the relationship between their reading and writing skills. This study used descriptive statistics to summarize the data and Pearson correlation analysis to test the hypothesis. The descriptive statistics revealed that the mean reading score was 64.95 with a standard deviation of 11.72, while the mean writing skill score was 63.45 with a standard deviation 10.34. Pearson correlation analysis revealed a significant positive correlation between reading and writing skills (r = 0.832, p < 0.001). These findings indicate that higher reading is strongly associated with better writing skills among EFL students. The implications of this study suggest that enhancing reading may contribute to improving writing skills, highlighting the interconnected nature of these language competencies in EFL education. Further research is recommended to explore the causal relationships and develop targeted instructional strategies that can simultaneously bolster reading and writing skills.